If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2a+6=a-7
We move all terms to the left:
2a+6-(a-7)=0
We get rid of parentheses
2a-a+7+6=0
We add all the numbers together, and all the variables
a+13=0
We move all terms containing a to the left, all other terms to the right
a=-13
| 5x+8-12x=-6x-2x-3 | | 6(2r-1)=-78 | | f(1/2)=2(1/2)+3 | | -(3x+-12)=48 | | -1n+10=3 | | 4(x−5)+2=4x−18 | | x-3/3=-4/1/2X3 | | (1.4)x=8 | | (x-9)^2=49 | | z/3+3=8/3 | | -x÷9=-8 | | −1+5x−15=−7(−6+8x)+3 | | 8+32y=24 | | 198=68-10x | | 16+2p=20 | | -29=7v+4(-8v-1) | | 3x-3x=17-5 | | x2−125=0 | | -2(x+3)=5(x+1) | | 0=x^2-2x-28 | | 2x+5(18)=6x | | -3(4x+3)+4*6x+1)=43 | | 4r+1=−2r+8 | | -1(3x+-12)=48 | | 116=4(5-6x) | | -5(5x-5)+3=-25x+28 | | 7c+12=-4c(78+12) | | 16x^2-56x+37=0 | | 1/4+x-1/3=2/3+3+1/4 | | -1/4w=7 | | 33=4x-7x+6 | | 4=4(x+3) |